The effect of Trump tariffs on Mexico and Canada - Lisandra Flach; Andreas Baur (CESifo GmbH, 2025)
US President Donald Trump has recently announced that tariffs on US imports from Canada and Mexico will take effect on March 4, 2025. This policy brief shows that the US tariffs would have a large impact on the North American neighbors. In the event of retaliation, all sectors of the economy (services, agriculture, and industry) in the three directly affected countries, including the US economy, would experience value-added losses. Moreover, in terms of trade flows, Canada would have to expect a long-term permanent decline in total exports of up to 28%, while Mexico could see a drop of more than 35% and the US of 22%. The close ties with the US due to their geographical location and the sectoral structure of their bilateral trade flows make it harder for Mexico and Canada to divert trade flows to other trade partners. Now more than ever, they should act to diversify their trade relations.
Keywords: 330; Zollpolitik; Branche; Wirkungsanalyse; Simulation; USA; Mexiko; Kanada